Hubungan Persepsi Ibu Dan Dukungan Suami Dengan Tingkat Kecemasan Pada Ibu Hamil Dalam Menghadapi Proses Persalinan: Relationship Between Maternal Perception and Husband’s Support with Anxiety among Pregnant Women Facing Childbirth - Arif, Ria Verti Sandika; Ningsih, Listya; Mulyadi, Eko; Permatasari, Dian; Huzaimah, Nailiy (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Anxiety among pregnant women in facing the childbirth process remains a maternal health problem as it can affect psychological readiness, the course of labor, and the well-being of both mother and fetus. Lack of support, inaccurate perceptions, and fear of labor pain often exacerbate anxiety experienced by pregnant women. This study aimed to determine the relationship between maternal perception and husband’s support with anxiety levels among pregnant women in facing the childbirth process at UPTD Puskesmas Jrangoan.        This study employed a correlational analytic design with a population of 33 pregnant women, from which 30 respondents were selected using simple random sampling. The research instrument was a questionnaire, and data were analyzed using the Spearman rank test.          The results showed that most pregnant women had good perceptions regarding childbirth, with 18 respondents (60.0%). In terms of husband’s support, the majority of pregnant women received good support from their husbands, totaling 21 respondents (70.0%). Anxiety levels among pregnant women indicated that half of the respondents experienced moderate anxiety, amounting to 15 respondents (50.0%). There was a significant relationship between maternal perception and anxiety levels among pregnant women in facing childbirth at UPTD Puskesmas Jrangoan, Sampang, with a p-value of 0.000 (<0.05). There was also a significant relationship between husband’s support and anxiety levels among pregnant women in facing childbirth at UPTD Puskesmas Jrangoan, Sampang, with a p-value of 0.007 (<0.05).          These findings indicate a significant relationship between husband’s support and anxiety levels among pregnant women, where better husband’s support is associated with lower levels of maternal anxiety.